2017
DOI: 10.1007/s00268-017-4356-1
|View full text |Cite
|
Sign up to set email alerts
|

High Elective Surgery Cancellation Rate in Malawi Primarily Due to Infrastructural Limitations

Abstract: This study demonstrates a high case cancellation rate at a tertiary hospital in Malawi, attributable primarily to infrastructural limitations. These data provide evidence that investments in medical infrastructure and prevention of workforce brain drain are critical to surgical services in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 25 publications
1
37
2
3
Order By: Relevance
“…Cancellation of elective operation on the intended day of surgery (DOS) is considered when a patient’s name has appeared on the list for surgical operations but the operation was not done on the intended scheduled date [ 1 ]. DOS cancellations are a world-wide problem, ranging from 0.37–28% in developed [ 2 9 ] and from 11 to 44% in developing countries [ 10 – 14 ]. It can be avoidable and non-avoidable [ 15 ] and avoidable cancellations were the commonest [ 4 , 16 , 17 ].…”
Section: Back Groundmentioning
confidence: 99%
“…Cancellation of elective operation on the intended day of surgery (DOS) is considered when a patient’s name has appeared on the list for surgical operations but the operation was not done on the intended scheduled date [ 1 ]. DOS cancellations are a world-wide problem, ranging from 0.37–28% in developed [ 2 9 ] and from 11 to 44% in developing countries [ 10 – 14 ]. It can be avoidable and non-avoidable [ 15 ] and avoidable cancellations were the commonest [ 4 , 16 , 17 ].…”
Section: Back Groundmentioning
confidence: 99%
“…Besides, management strategies or surgical settings might be similar in developing countries, but lower than a study conducted in Nigeria [23], Uganda [35] and Malawi [21]. This discrepancy might be due to ndings of cancellation varying widely by study design; hospital type, country, and capacity; patient type (inpatients vs. outpatients).…”
Section: Discussionmentioning
confidence: 91%
“…Based on the estimation of the reason for elective surgical case cancellation, the most common identi ed reason was administration-related reasons. The same report from the Kingdom of Saudi Arabia [17], Jordan [18], Uganda [35], and Malawi [21] showed that administration-related reasons found the most common reasons of elective surgical case cancellation. This might be due to the reality is that surgical case cancellation can result in the nancially under-utilization of theatres [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Basic infrastructure for surgery is frequently in short supply, limiting the consistency with which healthcare facilities can provide basic surgical care42 ; as an example, running water was only available in 50% of Gambian health facilities,43 and oxygen supplies with masks and tubing were available in only 26% of Rwandan health facilities 44. High rates of delayed or cancelled procedures in LMICs have been shown to arise through both poor infrastructure45 46 and equipment shortages 46…”
Section: Need Access and Qualitymentioning
confidence: 99%